What Is the Level of Savings Needed for High-Technology Export Led Growth? - Yılmaz, Ebru Gül (Ekonomika, 2024)
High-tech export-led growth is an important determinant in terms of having a milestone feature for the level of development of countries. Although the restrictions arise from recent literature, it is obvious that countries, like Korea with 35.7% the high-technology product export ratio and China with 31.3%, that have set a strategy on the high-technology export-led growth could have managed to achieve what they aimed to have. It is obvious that to make any investment in high-technology products, a certain level of savings should be achieved. The purpose of this paper is to determine the savings level that is necessary for achieving a high-technology export level for economic growth. The motivation arises from the willingness to shed light on policymakers on their way to achieve the high-technology export-led growth. Sixteen countries with high-technology product export levels higher than the World’s average are chosen in order to test the HXT export-led growth strategy at the initial stage. The period of 2007–2020 has been chosen due to the availability of the data. After achieving the result that there is a bidirectional casualty relationship between HTX and economic growth, by using the threshold regression model it is concluded that after achieving the savings level of 38.73%, countries can create an increase in their HTX level. And this is a very important output for policymakers for setting their strategies for the high-technology export-led growth. Hence the main aim of the policymakers is to increase welfare level of citizens, they should aim to reach 38.73% in order to achieve the high-technology export-led growth. After reaching this savings level they will have a chance to make investments for producing high-technology products by routing their savings to research and development and getting patents. In this way, they will have a chance to increase the welfare levels with the HTX-led growth strategy.
Keywords: High-technology export-led growth; saving level; Dimutrescue and Hurlin Casualty; Threshold Regression; Economic Development